Kepemimpinan Melayani Pemimpin Tongkonan Toraja menurut J. Oswald Sander - Herlina Buratasik; Willyam Ma'dika; Merlin Kaura; Yayan Wijaya; Naftali Ninggrum Tarra (Sukacita : Jurnal Pendidikan Iman Kristen, 2026)
This research analyzes the application of J. Oswald Sanders' servant leadership concept to tongkonan (traditional house) leadership in Toraja society. The background of this study is the presence of authoritarian leadership tendencies among to parenge (tongkonan leaders) who prioritize personal power over community service and empowerment. This research employs a qualitative approach through literature review, analyzing academic articles, research journals, and theological sources to understand the relevance and applicability of Sanders' principles within the Toraja cultural context. The findings reveal that Sanders' servant leadership, which is grounded in spiritual discipline and community empowerment, represents a viable alternative for reconstructing tongkonan leadership from an authoritarian model to a collegial model. However, implementing this model faces structural challenges due to the transformation of tongkonan's functions and the intrusion of formal government systems. In conclusion, Sanders' principles can be applied to tongkonan leadership through institutional reconstruction that combines traditional Toraja values with transparent and accountable leadership practices, thereby creating leadership that is simultaneously serving and empowering the community.